Long-Term Outcome of Liver Transplantation in HIV-1-Positive Patients: 15-Year Follow-Up. (25th December 2013) - Yamamoto, Shinji; Schwarcz, Robert; Weiland, Ola; Oksanen, Antti; Wernerson, Annika; Söderdahl, Gunnar; Sönnerborg, Anders; Ericzon, Bo-Göran
Abstract : Liver transplantation (LT) for patients with human immunodeficiency virus type-1 (HIV-1) infection has been associated with poor outcome. However, after the introduction of the highly active antiretroviral therapy, short-term patient survival after LT has improved significantly. We examined the long-term outcome of HIV-1-positive patients who underwent LT. Medical records were analysed in nine HIV-1-positive LT patients who underwent LT from August 1998 to May 2012. Eight were known to be HIV-1 positive at the time of listing for LT and had end-stage liver disease (ESLD) due to hepatitis C. One patient had primary biliary cirrhosis, and primary HIV-1 infection was found at the date of LT. Seven of the nine patients remain alive to date. So far, three have survived more than 12 years after LT. The overall patient survival rate for both five and 10 years is 77.8%. Four patients experienced acute rejection and six acquired biopsy-confirmed HCV recurrence. HIV-1 replication was effectively blocked during follow-up in all patients. We conclude that long-term survival of HIV-1-positive patients after LT can be achieved. Our study suggests that LT can offer an effective treatment option in selected HIV-1 infected patients with ESLD.